NMR characterization and dynamics of vanadium(V) complexes with tripod (hydroquinonate/phenolate) iminodiacetate ligands in aqueous solution - Drouza, Chryssoula; Stylianou, Marios; Keramidas, Anastasios D. (My University, 2009)
Reaction of NH 4VO 3 with (phenolate/hydroquinonate) iminodiacetate tripod ligands in aqueous solution in the pH range 7-8 results in the isolation of three new dioxido vanadium(V) complexes, one dinuclear (NH 4) 4{(V VO) 2[μ-bicah(6-)-N,O,O, O]}.8H 2O, (H 6bicah, 2,5-bis[N,N'-bis(carboxymethyl) aminomethyl]-hydroquinone), and two mono - nuclear (NH 4) 2{(V VO) 2[Hcah(3-)-N,O,O,O].2H 2O, (H 4cah, 2-[N,N'-bis(carboxy - methyl)aminomethyl]-hydroquinone) and (NH 4) 2{(V VO)[Hcacp(3-)-N,O,O,O]} 4H 2O, (H 4cacp, 2-[N,N'-bis(carboxymethyl)aminomethyl]-4- carboxyphenol). The 51V, 1H, and 13C NMR spectra in D 2O show the coordination environment of vanadium in the above complexes to be octahedral, with four out of six positions to be occupied by the two carboxylate oxygen, one hydroquinonate oxygen, and one amine nitrogen atoms of the tripod ligand. The two acetate arms are in cis position to each other. Variable-temperature 1H and 13C NMR measure ments show that the complexes are kinetically labile. An intramolecular exchange that proceeds through the opening of the phenolate/hydroquinonate chelate ring has been revealed by 2D{ 1H} NMR EXSY (exchange spectroscopy)
Keywords: University of Cyprus; Exchange; Transferrin; Tyrosine; Vanadium